MANAJEMEN BUDAYA RELIGIUS, BERPRESTASI, DAN PEDULI LINGKUNGAN DI SEKOLAH MENENGAH ATAS - Sukur, Puji; Nurlaili, Nurlaili; Sugeng, Sugeng (Universitas Negeri Surabaya, 2023)
This study aims to describe: 1) planning, 2) organizing, 3) implementation, 4) monitoring of religious culture, achievement, and care for the environment. This research is a qualitative research with a case study type. The research location is at SMA YPVDP Bontang. Research informants included school principals, vice principals, teachers, students, and parents. Collecting data using interview techniques, observation and document study. Data analysis uses an interactive model which includes condensation, data presentation, and drawing conclusions. Test the validity of the data using triangulation of sources and techniques. The results of the research are: 1) Planning is done before the new school year. The program is planned through environmental analysis that is adjusted to the school's vision and mission. Then make an activity plan and composition of the committee. The activity plan is discussed with the entire teacher council; 2) Organizing is done by selecting coordinators and committees. The coordinator provides facilities and infrastructure and schedules activities; 3) Implementation is carried out by instilling beliefs and assumptions in all school members about the importance of the program. The school gives awards to school members who carry out activities well. Making posters and slogans is intended to increase the motivation of school members; 4) Supervision is carried out by the school principal, vice principal, and activity coordinator. Supervision is carried out to obtain supporting and inhibiting data as well as any efforts made so that the implementation of the culture can run well.